Modeling the Cognitive Development Based on Fine Motor Skills in Preterm and Full‐Term Toddlers Using Lasso Regression - Ramazan Yildiz; Ayse Yildiz; Onur Camli; Bulent Elbasan (Brain and Behavior)
ABSTRACT Background The purpose of this study was to investigate the relationship between fine motor skills and cognitive development in preterm and term toddlers aged 12–15 months. Methods A total of 150 participants, 79 preterm, and 71 term toddlers, were assessed using the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley‐III), for cognitive development and the Peabody Developmental Motor Scales, Second Edition (PDMS‐2), for fine motor skills. The relationship between fine motor skills and cognitive development was examined with the lasso regression model. Results The study revealed that fine motor skills, particularly grasping, significantly influence cognitive development, with preterm toddlers demonstrating lower scores compared to term peers. Additionally, prenatal and perinatal factors, including gestational age and birth weight, were found to correlate with cognitive outcomes. Conclusions These findings emphasize the importance of integrating motor skill‐based interventions into early childhood programs to enhance cognitive and overall developmental outcomes. Future research should explore the causal mechanisms underlying this relationship.